Study On Pattern Of Obsessive Behaviors And Thoughts In A State Of Anxiety In Teenagers - Zaheen Baig Sajjad; Yousra Siddique; Aisha Tariq; Qudsia Suleman; Nayab Ashfaq (Journal of Bahria University Medical and Dental College)
Objective: To determine pattern of obsessive behaviors and thoughts in a state of anxiety in teenagers (14-18 years) of age.